Gambaran Emotional Focused Coping dalam Menyusun Skripsi pada Mahasiswa Program Studi Bimbingan dan Konseling Universitas Sultan Ageng Tirtayasa - Nida Hakimah; Rochani Rochani; Putri Dian Dia Conia (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2022)
College students are in a transition period from late adolescence to adulthood or called early adulthood. Unstable early adulthood can cause emotional tension, especially for thesis writing college students. Coping strategy that focuses on emotion or emotion focused coping is one of the treatments that can reduce college student stress when compiling a thesis. The purpose of this study is to find out the description of Emotional Focused Coping in college students who are preparing a thesis. The reason for doing this research is as a source of information for lecturers, counselors or college students to provide mentoring activities in order to prevent stress on college students in the preparation of the thesis. And can provide some counseling services for college students who are experiencing stress in the preparation of the thesis. This study uses descriptive quantitative methods. Based on the results of research that has been done, the description of emotional focused coping on Guidance and Counseling Untirta students at most tends to be quite good at 72% or as many as 64 college students from 89 college student samples. 27% or 24 college students were in the good category of emotional focused coping and 1% or 1 college student was in the bad category. Keywords: Emotional Focused Coping, Early Adulthood, Thesis